2022
DOI: 10.3390/ijms232415449
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate Alleviates Adult Neurogenesis Disruption in Hippocampus and Olfactory Bulb and Spatial Cognitive Deficits Induced by Intracerebroventricular Streptozotocin Injection in Young and Aged Rats

Abstract: The disorder of adult neurogenesis is considered an important mechanism underlying the learning and memory impairment observed in Alzheimer’s disease (AD). The sporadic nonhereditary form of AD (sAD) affects over 95% of AD patients and is related to interactions between genetic and environmental factors. An intracerebroventricular injection of streptozotocin (STZ-ICV) is a representative and well-established method to induce sAD-like pathology. Dimethyl fumarate (DMF) has antioxidant and anti-inflammatory prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…In behavioral terms, the initial two weeks following STZ administration were characterized by progressive and enduring deficits in learning and memory, which persisted for up to 12 weeks after infusion [35]. Numerous studies have shown that memory impairments become well-established 21 days after STZ administration [2,3,16,36]. Within this timeframe, deficits in rodent memory have consistently been observed through tests such as the ORT [36], the inhibitory avoidance test [37], and the Y-maze test [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In behavioral terms, the initial two weeks following STZ administration were characterized by progressive and enduring deficits in learning and memory, which persisted for up to 12 weeks after infusion [35]. Numerous studies have shown that memory impairments become well-established 21 days after STZ administration [2,3,16,36]. Within this timeframe, deficits in rodent memory have consistently been observed through tests such as the ORT [36], the inhibitory avoidance test [37], and the Y-maze test [3].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, this study investigated the involvement of acetylcholinesterase (AChE) activity. To mimic the sporadic non-hereditary form of AD, which is the most common category affecting patients and is related to interactions between genetic and environmental factors [16], low doses of STZ were used to induce this well-established model through an icv injection capable of inducing a pathology similar to AD [3,16].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effects exhibited by DMF were more significant in older rats compared to young animals ( Majkutewicz et al, 2018 ). More recently, DMF was demonstrated to reduce the number of lymphocytes and the serum levels of IL-6 and IFN-γ ( Wrona et al, 2022 ), and to improve neurogenesis and BDNF-related neuroprotection ( Kurowska-Rucińska et al, 2022 ) in the same STZ-induced model. Transgenic animal models of amyloidosis were used to test neuroprotective properties of DMF, leading to conflicting results.…”
Section: Novel Potential Pharmacological Applicationsmentioning
confidence: 99%